Efektivitas Penggunaan Sistem Manajemen Pembelajaran dalam Meningkatkan Kualitas Pembelajaran di Madrasah - Muhammad Wira Prabowo (Insan Zenius Ilmiah, 2026)
This study aims to assess the effectiveness of using a Sharia-based Learning Management System (LMS) to support learning in Islamic schools. The main focus of this study is to identify the limitations of conventional LMSs in accommodating Islamic values ​​and to explore the contribution of Sharia-based LMSs in shaping the character of religious and noble students. The approach used was qualitative with library research methods, involving the analysis of various academic literature related to Islamic education and learning technology. Data were collected through an in-depth review of books, journals, and policy documents, then analyzed descriptively, critically, and thematically. The results show that conventional LMSs do not fully meet the needs of holistic Islamic education because they only focus on technical aspects. In contrast, Sharia-based LMSs have proven more effective in integrating spiritual values ​​through features such as prayer reminders, Islamic content, and etiquette-based communication ethics. This LMS not only improves the efficiency of online learning but also strengthens the development of students' Islamic character. Therefore, the implementation of a Sharia-based LMS is a strategic step in addressing the challenges of digitalization while maintaining the integrity of Islamic values ​​in education.